A Choice Behavior Model of Bike-Sharing Based on User Perception, Psychological Expectations, and Loyalty. (14th April 2022) - Xue, Xingjian; Wang, Zixu; Liu, Xuejiao; Zhou, Zhou; Song, Rui
Abstract : In the midst of sharing concepts, bike sharing has made innovative changes to people's travel modes. Providing high-quality services is essential to promoting the usage of bike sharing and to reducing traffic congestion by shifting people away from private car use. This research explores the factors that influence users' selection of bike sharing as a transportation mode by identifying and describing relationships to user perception, psychological expectations, and loyalty. The effects of value identity, convenience, economy, comfort, perceived safety, travel characteristics (TC), and sociodemographic factors (SD) on the selection and usage of bike-sharing systems in Changsha, China, were analyzed. The mediating effect of user satisfaction (US) on the relationship between perceived quality (PQ) and use loyalty was examined. A total of 700 questionnaires were distributed at 20 bike-sharing locations, to which 569 users effectively responded. The results of the analysis indicate that loyalty to bike sharing was predicted by all of the studied constructs except for gender. The results of this study help us better understand the influencing factors of bike-sharing usage and can aid policymakers in formulating effective guidance strategies for bike-sharing travel demand based on a model structure.